THU0181 Antibodies to Etanercept and Adalimumab in Rheumatoid Arthritis Inadequate Responders and Clinical Outcomes after an Active Switch to Infliximab. (23rd January 2014) - Pool, C.; Shankar, G.; Schantz, A.; Gunn, G.; Bolce, R.; Leirisalo-Repo, M.; Wang, J.; Goldman, J.; DeHoratius, R.; Fleischmann, R.; Decktor, D.
Abstract : Objectives: To determine if RA patients (pts) who had an inadequate response to ETN or ADA& developed antibodies (Abs) to ETN or ADA responded clinically in RESTART after switching without a washout to IFX & if the presence of Abs to ETN or ADA correlated with differences in the levels of IFX or Abs to infliximab(ATI) compared to pts who had not developed Abs to ETN or ADA. Methods: RESTART is a Ph4, multicenter, open-label, assessor-blinded, active switch study of IFX+MTX (methotrexate) in pts with active RA who had an inadequate response (DAS28 score≥3.6 & ≥ 6 SJC & TJC) to ETN or ADA+MTX. EULAR response was evaluated at wk10 post-induction (1۫ endpoint). Pts adequately responding by EULAR criteria remained on IFX 3mg/kg; incremental increases in IFX dose in pts not achieving/maintaining EULAR response occurred at wks14 &/or 22, with final efficacy assessment at wk26. Assays were developed to measure Abs against ADA, ETN & IFX. Abs to anti-TNFs were measured at wks 0, 14 & 26 for ADA & wks0, 6, 14 & 26 for ETN & IFX. IFX levels were measured at wks 0, 6, 14 & 26. Results: 71%(88/124) of ETN inadequate responders had developed Abs to ETN (median titer=1280) & 50.6%(40/79) of ADA inadequate responders had developed Abs to ADA (median titer=320) through 26wks. Of these pts, 40.3%(50/124) of ETN pts & 46.8%(37/79) of ADA pts had measureable Abs before exposure to IFX. 195 pts had samples available for ATI testing, of which 24 pts(12.3%) had detectable ATI. Of these 24 pts, 23 had evidence of prior Abs to ETN(12/12) or ADA(11/12). (Incidence of ATI should not be directly compared to that of anti-ETN or anti-ADA here). Although no cross-reactivity was observed between anti-ADA Abs & IFX, the median wk26 serum conc of IFX was significantly lower in those pts who had developed Abs to ADA vs those who had not (2.1 mg/mL vs 11.9 ug/mL; p<0.0001) & contrasted with pts with or without Abs to ETN (8.8 ug/ml vs 11.7 ug/ml, resp; p = 0.4768). In pts who received IFX dose escalation to 5 or 7 mg/kg, the anti-ADA + pts who were ATI - had a median wk26 IFX serum conc (1.8ug/ml) lower than that observed for the dose escalated pts who were anti-ADA - (13.9ug/ml). Overall, the combined EULAR responses at wks10 & 26 were 49.7% & 51.8%, resp. Pts with Abs to ADA showed lower EULAR responses to IFX early on, but following incremental dose increases of IFX, these pts reached responses by wk26(55.3%) similar to pts who were anti-ADA - (59%). Conclusions: Although Abs develop in 6% & 5% of adult pts treated with ETN & ADA (ETN PI 2011, ADA PI 2002, resp), in this pt population of refractory RA pts who had an inadequate response to either ADA or ETN, the majority of pts had developed moderate to high titer Abs to either ETN or ADA. In these pts, 12.3% developed ATI through 26wks after switching to IFX. Since no cross-reactivity was observed between anti-ADA Abs & IFX, the data suggest that some pts who developed Abs to ADA cleared IFX more rapidly than those pts who were anti-ADA - and did so independent of ATI. Overall, a majority of IFX-treated pts demonstrated a EULAR response by wk26 regardless of the presence of Abs to ETN, ADA or IFX. Disclosure of Interest: C. Pool Employee of: Janssen Services, LLC, G. Shankar Employee of: Janssen R&D, LLC, A. Schantz Employee of: Janssen R&D, LLC, G. Gunn Employee of: Janssen R&D, LLC, R. Bolce Employee of: Janssen Services, LLC, M. Leirisalo-Repo Grant/research support from: Janssen Services, LLC, J. Wang Employee of: Janssen R&D, LLC, J. Goldman Grant/research support from: Janssen Services, LLC, R. DeHoratius Employee of: Janssen Services, LLC, R. Fleischmann Grant/research support from: Janssen R&D, LLC, D. Decktor Employee of: Janssen Services, LLC